PRIORITAS TANAMAN REVEGETASI PASCATAMBANG BATUBARA BERDASARKAN NILAI KELAYAKAN EKOLOGI - Kissinger Kissinger (Lambung Mangkurat University-Indonesia, 2022)
Post-mining reclamation includes various activities of structuring, restoring, and improving environmental quality. Revegetation contains replanting activities that are part of post-mining reclamation. Several considerations are needed in determining the choice of plant species for revegetation activities. This study aims to determine the order of priority for the selection of revegetation plant species based on criteria and indicators of ecological value. The research location was in the revegetation area of PT. Adaro Site Tanjung, South Kalimantan. A total of 6 measurement plots (40mx25m) were made using purposive sampling method in determining the selected measurement plots. Each measurement plot was divided into 4 measurement sub plots to measure the number of species, number of individuals, diameter and height of revegetation plants. The indicator criteria used as an analytical tool contain 6 criteria and 8 indicators. The eight indicators are the contribution of the species diversity index, growth percent, number of individuals/ha, dominance, species authenticity, canopy cover, natural introduction of new plants, and the rate of weathering of litter. The revegetation plant species assessed were Akasia (Acacia mangium), Johar (Cassia siamea), and Sengon (Paraserianthes falcataria). Data were analyzed quantitatively through scoring against the total value of the indicators or categories made. The order of priority for revegetation plants is P.falcataria (score 24 = high score), Johar (score: 23 = high score), and Akacia (score: 19 = low score). Ecological feasibility indicator criteria developed in this study can be used as a model for the selection of species to be developed in post-coal mining revegetation area